Bidentate auxiliary-directed alkenyl C–H allylation via exo-palladacycles: synthesis of branched 1, 4-dienes. Issue 90 (28th October 2019) - Shen, Cong; Lu, Xiunan; Zhang, Jian; Ding, Liyuan; Sun, Yaling; Zhong, Guofu
Abstract : An alkenyl C–H allylation by exo -palladacycle is demonstrated to produce branched skipped dienes, employing alkenyl amides and allyl carbonates. Abstract : An alkenyl C–H allylation by an exo -palladacycle intermediate is demonstrated, employing unactivated ( Z )-alkenes and allyl carbonates. With the use of an 8-aminoquinoline (AQ) derived amide as the directing group, the N, N -bidentate-chelation-assisted C–H activation protocol proceeded under mild and oxidant-free conditions with excellent selectivity. The utility of this approach is demonstrated by the preparative scale, selective conversion of inseparable Z / E alkenes and ready removal of the amide auxiliary to provide the corresponding ester.